Gratifications for Social Media Use in Entrepreneurship Courses: Learners’ Perspective - Wu, Yenchun; Song, Dafong (Frontiers in Psychology, 2019)
Abstract The purpose of this study is to explore uses and gratifications on social media in entrepreneurship courses from the learners' perspective. The respondents must have participated in government or private entrepreneurship courses and joined the online group of those courses. Respondents are not college students, but more entrepreneurs, and their multi-attribute makes the research results and explanatory more abundant. A total of 458 valid data was collected. The results of the survey revealed four gratification factors namely trust, profit, learning, and social in online entrepreneurial groups. It is also found that the structures and of the four gratification factors vary in three social media (Line, Facebook, and WeChat) and ''trust'' outranks other factors. Most of the entrepreneurs' business is "networking business", and the business unit is mostly "micro". In terms of the trust factor, there are significant differences among the three social media. In short, the two gratification factors of trust and profit can be seen as specific gratifications for online entrepreneurial groups, especially the trust factor, which deserves more attention in the further research of online entrepreneurial courses on social media.